High School Students' Perspectives of Participating in a STEM-Related Extracurricular Programme - Mtika, Peter (Frontiers in Education, 2019)
This article reports on secondary school students’ perspectives of participating in science, technology, engineering and mathematics (STEM) related extracurricular activities in six secondary schools in Scotland. The extracurricular activities aimed at supporting students in developing knowledge of STEM subjects and confidence in their preparation for high school examinations, post-secondary schooling and the world of work. The study used a mixed-methods design. This entailed collecting data using qualitative semi-structured interviews, focus group discussion and a quantitative questionnaire. Findings indicate that students viewed extracurricular activities positively. They felt that the activities they participated in made a difference in their overall development. STEM related extracurricular activities provided students with relevant subject knowledge, wider learning opportunities and confidence in their own abilities, thereby contributing towards academic and social development. Students also reported increased knowledge of post-schooling opportunities. The activities resonated with the Scottish Curriculum for Excellence (CfE), thereby complemented formal learning.